2020
DOI: 10.3389/fnhum.2020.00080
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Alterations in Hemodialysis Patients: A Voxel-Based Morphometry and Functional Connectivity Study

Abstract: Structural and functional brain alterations have been always observed in end-stage renal disease (ESRD) patients undergoing hemodialysis. The present study aimed to investigate the gray matter volume (GMV) changes in hemodialysis patients compared with those noted in healthy subjects, as well as explore the associated functional connectivity alterations based on the abnormal GMV regions. The experiments revealed the effects of regional morphometry aberrance on the brain functional integrity. A total of 46 hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
2
20
1
Order By: Relevance
“…We also detected atrophy of the left hippocampus, albeit without Bonferroni correction. However, in contrast, it is different from our research results, and a recent study found significantly higher bilateral thalamus volumes in hemodialysis patients compared with HCs, although their results on the caudate and amygdala volumes were similar to our observations ( Jin et al, 2020 ). Previous researchers found that compared with HCs, patients with minimal nephro-encephalopathy ESRD had lower brain volumes of the right amygdala and hippocampus, and those with non-nephro-encephalopathy ESRD had higher brain volumes of the right caudate and right thalamus ( Zhang et al, 2013 ).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…We also detected atrophy of the left hippocampus, albeit without Bonferroni correction. However, in contrast, it is different from our research results, and a recent study found significantly higher bilateral thalamus volumes in hemodialysis patients compared with HCs, although their results on the caudate and amygdala volumes were similar to our observations ( Jin et al, 2020 ). Previous researchers found that compared with HCs, patients with minimal nephro-encephalopathy ESRD had lower brain volumes of the right amygdala and hippocampus, and those with non-nephro-encephalopathy ESRD had higher brain volumes of the right caudate and right thalamus ( Zhang et al, 2013 ).…”
Section: Discussioncontrasting
confidence: 97%
“…These different findings are likely related to differences in study patients and methods used. For example, some researchers used VBM to analyze subcortical volumes instead of the volumetric analysis methods used in our study ( Prohovnik et al, 2007 ; Zhang et al, 2013 ; Jin et al, 2020 ). Moreover, our study subjects differed from those of previous studies; the previous study selected patients with ESRD with non-nephro-encephalopathy, whereas the patients in our study had general cognitive and sleep disorders ( Zhang et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients in our study displayed lower between-network connectivity at the cingulate and postcentral gyri in SN, while insula-thalamus connectivity was clearly increased in the patients with ESRD receiving PD ( Table 3 ), which has never been reported before. In contrast, a recent study that focused on patients receiving HD found hypo-connectivity in the thalamo-cortical network ( 16 ). Based on the observations, the SN could be a potential network susceptible to the changes of between-network connectivity in the patients with ESRD receiving PD; however, further investigation is needed to delineate whether dialysis modalities affect the patterns of connectivity alterations.…”
Section: Discussionmentioning
confidence: 86%
“…Earlier, R-fMRI studies of patients with ESRD found decreased brain regional activity in a diffuse pattern over bilateral frontal, parietal, and temporal lobes, or impaired default-mode network (DMN) connectivity in the posterior cingulate cortex, precuneus, and medial prefrontal cortex (11,12), without mention of dialysis modality. Subsequent studies have identified different aspects of connectivity reduction in patients with ESRD (13)(14)(15)(16). Zheng et al observed the decreased connectivity to be predominantly related to the prefrontal lobe in patients with ESRD receiving hemodialysis (HD), which involves planning complex cognitive behavior (13).…”
Section: Introductionmentioning
confidence: 99%